Management of lung transplantation in the COVID‐19 era—An international survey. Issue 4 (5th November 2020) - Coiffard, Benjamin; Lepper, Philipp M.; Prud'Homme, Eloi; Daviet, Florence; Cassir, Nadim; Wilkens, Heinrike; Hraiech, Sami; Langer, Frank; Thomas, Pascal A.; Reynaud‐Gaubert, Martine; Bals, Robert; Schäfers, Hans‐Joachim; et al.
Abstract : It is unknown if solid organ transplant recipients are at higher risk for severe COVID‐19. The management of a lung transplantation (LTx) program and the therapeutic strategies to adapt the immunosuppressive regimen and antiviral measures is a major issue in the COVID‐19 era, but little is known about worldwide practice. We sent out to 180 LTx centers worldwide in June 2020 a survey with 63 questions, both regarding the management of a LTx program in the COVID‐19 era and the therapeutic strategies to treat COVID‐19 LTx recipients. We received a total of 78 responses from 15 countries. Among participants, 81% declared a reduction of the activity and 47% restricted LTx for urgent cases only. Sixteen centers observed deaths on waiting listed patients and eight centers performed LTx for COVID‐19 disease. In 62% of the centers, COVID‐19 was diagnosed in LTx recipients, most of them not severe cases. The most common immunosuppressive management included a decreased dose or pausing of the cell cycle inhibitors. Remdesivir, hydroxychloroquine, and azithromycin were the most proposed antiviral strategies. Most of the centers have been affected by the COVID‐19 pandemic and proposed an active therapeutic strategy to treat LTx recipients with COVID‐19. Abstract : This international survey reports on the worldwide impact of COVID‐19 on lung transplant programs at the early stage of the pandemic, showing a dramatic decrease of transplant activity and delineating strategies used to prevent, and treat COVID‐19 in lung transplant recipients.